Analysis of Controlling and Monitoring System Growth Hydroponic Plants Grace - Sitorus R P; Marzuki Marzuki (Bandar Lampung University (UBL), 2017)
Land on Earth at the present time more and more narrow, if people do not manage with optimal and efficient , Many urban residents who make a community greening or more known by the term GoGreen.This community is in the form of re-greening the city, but not a few who are not interested at all in this green movement because they feel bothered to do so, not least from those who are lazy andafraid dirty.The last few years have been a lot of movement as a solution Hydroponics gardening for residents in urban areas. Hydroponics is the art plant with water media that works as a soil substitutealternative media. Hydroponics is derived from the Greek, Hydroponic meaning hydro means water and ponous means work. Many types of hydroponics quick to handle the narrow land as it can bearranged vertically, one of its kind is NFT(NutrientFilmTechnique).